2014
DOI: 10.1080/09540121.2014.936820
|View full text |Cite
|
Sign up to set email alerts
|

Disability and HIV: a systematic review and a meta-analysis of the risk of HIV infection among adults with disabilities in Sub-Saharan Africa

Abstract: More than one billion people worldwide are estimated to be living with a disability. A significant proportion of them lives in Sub-Saharan Africa where they are reported to be at increased risk of HIV. However, quantitative evidence on this remains scarce. A systematic review and a meta-analysis of the risk of HIV infection among people with disabilities living in Sub-Saharan Africa were undertaken. We searched all published or unpublished studies and national surveys reporting HIV prevalence among adults with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 38 publications
1
56
1
Order By: Relevance
“…However, this does not indicate that they are free from HIV risk. There is evidence that it is a population at risk for HIV [12,28]. …”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not indicate that they are free from HIV risk. There is evidence that it is a population at risk for HIV [12,28]. …”
Section: Limitationsmentioning
confidence: 99%
“…A systematic review by De Beaudrap et al . found that persons with disabilities do not have a lower risk of HIV infection compared with the general population [12]. …”
Section: Introductionmentioning
confidence: 99%
“…The literature often refers to the "double burden" of being female and experiencing a disability. In reviews examining the risk for HIV among people with disabilities, women were found to be significantly affected (De Beaudrap et al, 2014;Groce et al, 2013;). Women with disabilities may experience difficulties in forming secure, lasting relationships, as women with disabilities may be perceived as a burden and not valuable spouses, with the result that women may be abused and abandoned by their spouses Kiani, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This is beginning to change, with a growing awareness of the equal, if not increased risk to HIV infection for people with disabilities. Comprehensive reviews looking at the risk for HIV among people with disabilities have been published elsewhere, and will not be reviewed again here (for such reviews see Groce et al, 2013, and De Beaudrap et al, 2014. Rather, an argument is made for how mainstream HIV prevention work and research does not adequately attend to the sorts of systemic barriers that exclude people with disabilities, which a more targeted, and critical approach could.…”
Section: Introductionmentioning
confidence: 99%
“…For example, severe mental illness has been shown to be an independent risk factor for other important non-communicable disorders such as cardio-metabolic diseases, albeit inconsistently in SSA studies [7]. Consistent associations are however reported between HIV/AIDS and poor mental health [8, 9] and chronic pain and poor mental health [10, 11]. Also the strong and often bidirectional relationships of mental disorders with substance use disorders and the associated increased risk for accidents and injuries emphasizes the critical role of a rigorous mental health policy in SSA [3].…”
Section: Introductionmentioning
confidence: 99%